Effect of Superoxide Dismutase (SOD) Supplementation on Plasma Levels of Malondialdehyde (MDA), Total Cholesterol and LDL Cholesterol in the Elderly - Dwi Ngestiningsih; Rejeki Andayani Rahayu; Lusiana Batubara (Journal of Biomedicine and Translational Research, 2019)
Background: Several various physiological functions in elderly people are diminished due to cell or tissue damage. One of the probable causes are oxidative stress yielded by free radicals.